Age-related Changes in DNA Methylation Status of hTERT Gene Promoter of Oral Epithelial Cells - Bezerra,Stephane Flaviane de Oliveira (2015)
The purpose of this study was to investigate the effect of aging on the DNA methylation status of two genes involved in tumorigenesis (telomerase gene hTERT and DNA repair gene- MLH1) and one in metabolism (methylenetetrahydrofolate reductase gene- MTHFR) in oral epithelial cells. DNA methylation analysis was performed by Methylation Sensitive Restriction Enzymes (MSRE) of healthy oral epithelial cells of child (6-10 years, n=21), young (20-25 years, n=19) and elderly (over 60 years, n=25). The results for the hTERT gene showed significant variation in the methylation frequency at CpG dinucleotides among the groups (p=0.0001), with the methylated condition more frequently in children and young people. In relation to MLH1 and MTHFR, no differences were observed among the groups and the unmethylated condition were present in most individuals (p>0.05). Thus, it was concluded that aging of oral epithelial cells was associated with hypomethylation of the hTERT gene promoter and this could be a promising marker for screening a set of age-related alterations.